Application of Surgical Protocols for the Treatment of Highly Irregular Astigmatism with Topographic Guided Ablation in a Case of Post-LASIK Ectasia - Motwani M; Agu E; Xu A; Yung M (International Medical Case Reports Journal)
Manoj Motwani,1 Emmanuel Agu,2 Albert Xu,2 Madeline Yung2 1Motwani Lasik Institute/Cornea Revolution, San Diego, CA, USA; 2Department of Ophthalmology, University of California San Francisco, San Francisco, CA, USACorrespondence: Madeline Yung, Email madeline.yung@ucsf.eduPurpose: To compare the outcomes of two different surgical planning strategies for topography-guided repair of post-LASIK ectasia.Methods: This is a case report of a patient presenting with post-LASIK ectasia. A retrospective chart review was used to collect details of the ophthalmic exam, as well as ocular imaging such as anterior segment optical coherence tomography and Scheimpflug corneal tomography. Treatment planning was performed initially with the Phorcides analytical engine, and then an enhancement was performed with the LYRA/San Diego Protocol. Epithelium-off corneal cross-linking was performed at 3.0 mW/cm for 30 minutes.Results: The patient initially presented with a remote history of LASIK and progressive left eye blurring. His uncorrected distance visual acuity (UDVA) was 20/40, with a corrected distance visual acuity (CDVA) of 20/25 with a manifest refraction of − 1.25 +1.75 × 180. His central corneal thickness was 529 μm, and corneal topography/tomography demonstrated inferior steepening of the left eye consistent with post-LASIK ectasia. He underwent simultaneous PRK and epithelium-off corneal cross-linking with a treatment plan by Phorcides of – 0.14 − 0.87 × 001. His vision stabilized at post-operative month 7 to a UDVA 20/40, CDVA 20/20, and manifest refraction of − 2.75 +3.50 × 005. He underwent PRK enhancement with a treatment plan by the San Diego Protocol of +0.00 – 1.15 × 094, with an outcome of UDVA 20/20, CDVA 20/20, and manifest refraction of − 1.00 +0.75 × 174.Conclusion: The LYRA/San Diego Protocol outperformed Phorcides in a case of corneal ectasia. With appropriate planning, patients with irregular corneas can achieve excellent refractive outcomes.Keywords: corneal cross-linking, post-LASIK ectasia, Phorcides, San Diego Protocol, topography-guided ablation